Keragaan Padi Hibrida pada Sistem Pengairan Intermittent dan Tergenang - Munarso, Yuniati Pieter (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
An experiment to evaluate growth and yield performance of rice hybrids planted in different irrigation system was conducted at the green house of the Indonesian Center for Rice Research in Sukamandi, Subang 2010.The experiment was arranged in a randomized block design with irrigation system (intermittent and continuous flooded) as first factor and genotype of hybrid (15 genotypes) as second factor, with 2 reps. Results showed that genotype was dominant determinant factor for several observed variables, i.e. plant height, total tillers, flowering and harvesting time, and root character (root volume) as well. Genotype acts as single determinant factor on paddy grain yield, and its yield components (total and percentage of filled grain). Yield observation showed that, this variable was significantly affected by hybrid genotype. Genotype G23 showed to be the highest yielding genotype. Rice grain yield was supported by yield components of total filled-grains and percentage of seed set, rather than panicle length. Intermittent treatment produced longer root. Meanwhile, continuous submerged produced shorter root with more branch.